Sensibilidade de variedades de milho (Zea mays) ao alumínio em solução - Lima, Daniel Luiz Sans de (Universidade Federal de São Carlos, 2011)
The influence of Al toxicity on the development of the root system and on the interference of nutrient absorption, typical of acidic soils, has been presented as one of the main causes of the low productivity of many crops of economic concern. The objectives of this study were: to evaluate the root development of maize plants, Dow 2B655, AG 8061 pro, Al Bandeirante, and DKB 747 varieties, in nutritive solution with different conditions of Al stress (0, 55, 111, 222, 444, and 666 µmol L-¹); examine morphological changes in the roots of maize seedlings through optical microscopy; verify the penetration of Al in the root tissue with the use of hematoxylin dye. The experiment was carried out under laboratory conditions, in a completely randomized design, with four replications. The results of root growth rate (cm day-1) were subjected to analysis of variance and compared by Tukey's test (p<0.05). Morphological parameters of Al in root tissues, indicated by staining, were explored in the form of images by photographic recording of observations under the optical microscope. The increase in the concentration of Al in solution caused a decrease in the rate of root elongation of all maize varieties. The critical concentration of Al in solution, which initiated the deterioration processes of the root apex, was 111 mol Al L-1. The main morphological changes in the roots, that is, the production of callose and the collapse and deformation of the hood, started from the critical concentration of 111 mol Al L-1 only in the AG 8061 variety. For the Al. Bandeirante, DKB 747, and Dow 2B655 mayze varieties, physiological injuries to the root apices were caused by concentrations of Al in solution greater than 444 mol Al L-1. The hematoxylin dye helped to indicate the accumulation and location of Al in the root tissue. The root biometry indicated that the Al. Bandeirante and Ag. 8061 mayze varieties were more tolerant to Al in solution, while the Dow 2B655 and DKB 747 varieties were the most sensitive. However, visual examination by the hematoxylin method and by optical microscopy indicated the following sequence of mayze varieties tolerance to Al in solution: Al Bandeirante > Dow 255 = DKB 747 > Ag 806.
Sensitivity of maize varieties (Zea mays) to aluminum in solution
Keywords: Fitotoxidez; Solos ácidos; Alumínio; Milho; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO